Functional and Structural Connectivity Between the Left Dorsolateral Prefrontal Cortex and Insula Could Predict the Antidepressant Effects of Repetitive Transcranial Magnetic Stimulation - Fu, Yixiao; Long, Zhiliang; Luo, Qinghua; Xu, Zhen; Xiang, Yisijia; Du, Wanyi; Cao, Yuanyuan; Cheng, Xiaoli; Du, Lian (Frontiers in Neuroscience, 2021)
Background: The efficacy of repetitive transcranial magnetic stimulation (rTMS) in depression is nonuniform across patients. This study aims to determine whether baseline neuroimaging characters can provide a pretreatment predictive effect for rTMS. Methods: Twenty-seven treatment-naive patients with major depressive disorder (MDD) were enrolled and scanned with resting-state fMRI and diffusion tensor imaging. Clinical symptoms were assessed pre- and post- rTMS. Functional and structural connectivity between the left dorsolateral prefrontal cortex (DLPFC) and bilateral insula were measured and the connectivity strength in each modality was then correlated to the clinical efficacy of rTMS. Results: When the coordinates of left DLPFC was located as a node in the central executive network, the clinical efficacy of rTMS was significantly correlated with the functional connectivity strength between left DLPFC and bilateral insula (left insula: r = 0.66; right insula: r = 0.65). The structural connectivity strength between the left DLPFC and left insular cortex also had a significantly positive correlation with symptom improvement (rs=0.458). Conclusion: This study provides implications that rTMS might act more effectively when the pretreatment functional and structural connectivity between the insula and left DLPFC is stronger.